Caseous Calcification of the Mitral Annulus: Mimic and Malady. (February 2019) - Shapeton, Alexander D.; Kumaresan, Abirami; Liu, David C.; Krajewski, Megan L.
Abstract : Supplemental Digital Content is available in the text.